SVM-Based Automatic Classification of Musical Instruments - Jing Liu; Lingyun Xie (2010 International Conference on Intelligent Computation Technology and Automation, 2010)
Instrumental music is often classified or retrieved in terms of instruments played in it. With a large database consists of Chinese traditional music and western classical music, this paper extracted several features to automatically classify Chinese and western instruments by SVM classifier, and analyzed the classification results.